Old Turtle - Douglas Wood (Duluth, United States Pfeifer Hamilton Publishers,US, 1992)
All of nature argues about the forms of God, so people are sent as a reminder of all that God is, although they do not seem to understand the message themselves.
Keywords: Circle Time - Faith / Spirituality / Healing -- Circle Time - Faith / Spirituality / Healing